Perceived child abuse and neglect in hospitalized children with special health care needs in Iran - Niloofar Bahrami; Maryam Tork-Torabi; Reza Sotoudeh; Mahboobeh Namnabati (Wolters Kluwer Medknow Publications, 2021)
Background: Child Abuse and Neglect (CAN) is an important public health concern. Nurses play a key role in caring for the children and keeping them safe from abuse and neglect. The aim of this study was to determine the rate of perceived CAN in Hospitalized Children with Special Health Care Needs (CSHCN) as well as the relationship between the rate and some effective factors. Materials and Methods: This is a descriptive cross-sectional study on 199 CSHCN aged 6-18 years old, admitted to the pediatric wards in an educational hospital, in Isfahan, Iran, in 2018. Children were selected through convenience sampling method and assessed for CAN through a child abuse questionnaire. The Pearson correlation coefficient and Kruskal-Wallis and Mann-Whitney U tests were used to analyze the data. The p values smaller than 0.05 were regarded as significant. Results: According to the findings, 173 children (86.93%) had perceived CAN, the average total score of which was 9.36 contributing commonly to malnutrition 3.01 (2.36) followed by psycho-emotional abuse 2.71 (1.76), neglect 1.62 (1.23), and physical 1.52 (1.08) and sexual 0.54 (0.31) abuse based on mean (SD). Statistical analysis indicated a significant effect of child's age, economic situation of the family, mother's education and occupation, and parents' illness on the total score of perceived CAN (p < 0.05). Conclusions: Malnutrition was found to be the most common type of perceived CAN. Therefore, parents and the health system are advised to prioritize nutritional needs when planning their nutrition.